Chapter V: The Influence of Monetary Policy on the Housing Boom (Quarterly Journal of Economics, 1941)
Journal Article Chapter V: The Influence of Monetary Policy on the Housing Boom Get access The Quarterly Journal of Economics, Volume 56, Issue 1_Part_2, November 1941, Pages 108–145, https://doi.org/10.1093/qje/56.1_Part_2.108 Published: 01 November 1941